THE EFFECT OF INDEPENDENCE, COMPETENCE, ACCOUNTABILITY AND WORK EXPERIENCE ON AUDIT QUALITY AT PUBLIC ACCOUNTING OFFICES IN MEDAN CITY - Afrizar Pane; Irene Febrianna Tarigan; Sunidar Laoli; Junita Sukmawati Zebua (RADJA PUBLIKA, 2023)
This contemplate directs to influence the chain reaction of home rule competence, accountableness and elbow grease acquaintance on scrutinize superiority at a universal accounting trueheart in Medan. The evaluation disposition euphemistic pre-owned therein evaluation is descriptive decimal method. The collections psychoanalysis disposition euphemistic pre-owned in this contemplate is statistical psychoanalysis disposition victimisationing IBM SPSS (Statistical combination for collective Science) ver 20 software. The inhabitant therein contemplate were auditors at KAP Medan, patch the exemplification in this contemplate was 38 auditors at KAP Medan. with purposeful distribution technique. The collections psychoanalysis euphemistic pre-owned is descriptive data, validness and dependability test, graeco-roman presumptuousness test, aggregate one-dimensional retrogression analysis, coefficient of steadfastness psychoanalysis and possibility testing. The consequences show: 1) sovereignty has a cocksureness and substantial chain reaction on scrutinize superiority at KAP in city 2) potency has a contradiction and undistinguished chain reaction on scrutinize superiority at KAP in city 3) accountableness has a cocksureness and substantial chain reaction on scrutinize superiority at KAP in city 4) acquaintance elbow grease has a cocksureness and substantial chain reaction on scrutinize superiority at KAP in city